MANAJEMEN KELAS DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PAI SISWA KELAS V SEKOLAH DASAR {STUDI KASUS DI SDN CIKAWUNG KEC. SINDANGBARANG-CIANJUR} - Mustakim, Mustakim; Ependi, Edi; Mardiana, Dhinny (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research examines classroom management in an effort to enhance the effectiveness of Islamic Religious Education (PAI) learning for fifth-grade elementary school students, with a case study at SDN Cikawung, Cianjur. The objectives are to describe the PAI teacher's classroom management strategies, identify supporting and inhibiting factors, and analyze their impact on learning outcomes and the PAI classroom atmosphere. The research uses a descriptive qualitative approach with a case study method. Data collection was carried out through participatory observation, in-depth interviews with the PAI teacher, school principal, and students, as well as documentation studies. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the PAI teacher at SDN Cikawung implements various classroom management strategies, including physical arrangement, time management, discipline, and learning motivation. These strategies are supported by teacher commitment, principal support, and student participation. Although there were obstacles such as limited facilities and differing student backgrounds, the effective implementation of classroom management significantly contributed to improved material comprehension, active student participation, and the creation of a conducive classroom atmosphere. This research concludes that classroom management is crucial in creating an optimal learning environment and is positively correlated with the achievement of learning objectives.